2010
DOI: 10.1111/j.1365-313x.2010.04363.x
|View full text |Cite
|
Sign up to set email alerts
|

ZmMYB31 directly represses maize lignin genes and redirects the phenylpropanoid metabolic flux

Abstract: SUMMARYFew regulators of phenylpropanoids have been identified in monocots having potential as biofuel crops. Here we demonstrate the role of the maize (Zea mays) R2R3-MYB factor ZmMYB31 in the control of the phenylpropanoid pathway. We determined its in vitro consensus DNA-binding sequence as ACC T / A ACC, and chromatin immunoprecipitation (ChIP) established that it interacts with two lignin gene promoters in vivo. To explore the potential of ZmMYB31 as a regulator of phenylpropanoids in other plants, its ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
236
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(245 citation statements)
references
References 79 publications
6
236
3
Order By: Relevance
“…This would suggest that DNA binding is also essential for its repressor function (Jin et al, 2000). Other subgroup 4 MYB factors are reported to directly bind target gene promoters (Jin et al, 2000;Fornalé et al, 2010;Shen et al, 2012;Bomal et al, 2014). We cannot rule out that mutation of the MYB182 bHLH-binding site also might have affected its DNA-binding ability, since Baudry et al (2004) had shown that the Arabidopsis MYB TT2 can only bind to its target gene promoter in yeast (Saccharomyces cerevisiae) in the presence of a bHLH or WDR factor.…”
Section: Myb182 Is a Repressor That Reduces Pa And Anthocyanin Accumumentioning
confidence: 99%
“…This would suggest that DNA binding is also essential for its repressor function (Jin et al, 2000). Other subgroup 4 MYB factors are reported to directly bind target gene promoters (Jin et al, 2000;Fornalé et al, 2010;Shen et al, 2012;Bomal et al, 2014). We cannot rule out that mutation of the MYB182 bHLH-binding site also might have affected its DNA-binding ability, since Baudry et al (2004) had shown that the Arabidopsis MYB TT2 can only bind to its target gene promoter in yeast (Saccharomyces cerevisiae) in the presence of a bHLH or WDR factor.…”
Section: Myb182 Is a Repressor That Reduces Pa And Anthocyanin Accumumentioning
confidence: 99%
“…ZmMYB31 downregulated several genes involved in the synthesis of monolignols and transgenic plants were dwarf and showed a significantly reduced lignin content with unaltered polymer composition. In addition, ZmMYB31 repressed the synthesis of sinapoylmalate and phenylpropanoid resulting in plants that were more sensitive to UV irradiation, and induced several stress-related proteins (Fornale et al 2010). …”
Section: Myb As Negative Regulatorsmentioning
confidence: 99%
“…Zea mays R2R3-MYB transcription factor (ZmMYB31), a direct repressor of caffeic acid 3-O-methyltransferase and Arabidopsis ferulate-5-hydroxylase genes, overexpression in Arabidopsis results in reduction in sinaopylmalate and lignin accumulation while enhancing accumulation of ferulic acid, coumaric acid, and anthocyanins (Fornalé et al, 2010). In addition, the colorless fruit peel y mutant in tomato was found to be a mutation causing down-regulation of SlMYB12, a transcription factor that acts as a positive regulator of an array of phenylpropanoid structural genes.…”
Section: Metabolites Analysis and Cmkfb Functionmentioning
confidence: 99%